Objetivo 13 "Acción Climática" en San Francisco de Campeche, México: Mejorando la resiliencia costera: Mejorando la resiliencia costera - Cruz Benítez, Enriqueta del Carmen; Rivera Arriaga, Evelia; Williams-Beck, Lorraine A.; Posada Vanegas, Gregorio; Ramos Miranda, Julia; Agraz Hernández, Claudia M.; Peña-Puch, Angelina del C. (Costas, 2025)
As a coastal city, San Francisco de Campeche, México (SFC) is innately vulnerable to the effects of climate change. Given this problem, life experiences, opinions, needs and proposal data collections provide a social diagnosis about how people perceive and act, when faced with climate adverse consequences, to enhance their resilience. Derived from those natural and cultural figures information we designed SFC’s Action Climate Program (ACP). This agenda directly addresses “Climate Action” sustainable development’s objective 13, target 3, by offering environmental education strategies and community collaboration and participation for design public policies and decision-making processes for coastal management resilience. We predict that correctly implementing this program will improve people’s capacity to respond and adapt to climate change effects. Moreover, active participation in decision making processes offers a second corollary to empower people to reduce risks that resolve nagging socioenvironmental issues in their coastal communities.